2020
DOI: 10.1155/2020/8886932
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Machine Learning in Intelligent Terrain Classification of Hyperspectral Remote Sensing Images

Abstract: To overcome the difficulty of automating and intelligently classifying the ground features in remote-sensing hyperspectral images, machine learning methods are gradually introduced into the process of remote-sensing imaging. First, the PaviaU, Botswana, and Cuprite hyperspectral datasets are selected as research subjects in this study, and the objective is to process remote-sensing hyperspectral images via machine learning to realize the automatic and intelligent classification of features. Then, the basic pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Nevertheless, all hope is not lost as several AI studies indicated that they used Botswana datasets in various areas. For instance; Hyperspectral images, Orapa diamond mine provided blasting datasets, and there is data available in the United Nations SDG data repository (Gaopale, et al, 2019;Li, et al, 2020;Mwitondi, et al, 2020;Seera & Lim, 2014).…”
Section: Data Availabilitymentioning
confidence: 99%
“…Nevertheless, all hope is not lost as several AI studies indicated that they used Botswana datasets in various areas. For instance; Hyperspectral images, Orapa diamond mine provided blasting datasets, and there is data available in the United Nations SDG data repository (Gaopale, et al, 2019;Li, et al, 2020;Mwitondi, et al, 2020;Seera & Lim, 2014).…”
Section: Data Availabilitymentioning
confidence: 99%
“…For example, disease detection (Jin et al, 2013), weed detection (Papp et al, 2021), and terrain classification (Li et al, 2020b). And because hyperspectral images contain a large amount of information and have a sizeable sparse data structure, researchers often use SVM methods as the primary modeling tool.…”
Section: Elasticnetmentioning
confidence: 99%
“…Remote sensing refers to the identification of planet earth by analyzing various physical events such as detecting electromagnetic radiation. The use of remote sensing is currently very widely used in various fields, including education (Botto et al, 2022;Li et al, 2020;Tiwari et al, 2021), industry (Hao et al, 2022), mining (Song et al, 2020), defense and security (Mehta et al, 2021), regional planning (Kumar et al, 2021), to the health sector (Ye, 2022).…”
Section: Introductionmentioning
confidence: 99%